2006
DOI: 10.1530/eje.1.02054
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin and the development of diabetes in patients with coronary artery disease and impaired fasting glucose

Abstract: Objectives: Adiponectin has insulin-sensitizing properties, and high adiponectin levels have been shown to be associated with reduced risk of developing diabetes. Patients with coronary artery disease (CAD) have relatively low adiponectin levels and high prevalence of glucose intolerance. The role of adiponectin in predicting the development of diabetes in this high-risk group has not been determined. The study aimed to determine whether baseline adiponectin levels predict the development of diabetes in a grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
13
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 26 publications
6
13
0
Order By: Relevance
“…26 Here we also showed that high baseline concentration of adiponectin was associated with lower risk for new-onset diabetes in patients with the MS. It should be noted that the randomly selected patients in the placebo and bezafibrate groups in our study present some minor differences regarding degree of obesity, insulin concentrations and use of angiotensin-converting enzyme inhibitors.…”
Section: Discussionsupporting
confidence: 59%
“…26 Here we also showed that high baseline concentration of adiponectin was associated with lower risk for new-onset diabetes in patients with the MS. It should be noted that the randomly selected patients in the placebo and bezafibrate groups in our study present some minor differences regarding degree of obesity, insulin concentrations and use of angiotensin-converting enzyme inhibitors.…”
Section: Discussionsupporting
confidence: 59%
“…Diabetes 57:980-986, 2008 A diponectin, the dominant secretory product of adipocytes, is a marker and perhaps a mediator of metabolic and cardiovascular disease risk (1)(2)(3)(4). In a number of case-control and cohort studies (1,(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15), adiponectin levels have been found to be inversely associated with insulin sensitivity, conversion to diabetes, and risk of myocardial infarction. These associations remain significant after adjustment for baseline measures of obesity, suggesting that adiponectin reflects components of metabolic and vascular risk beyond those encompassed in obesity alone.…”
mentioning
confidence: 99%
“…Although proposed as an abundant cytokine generated by adipose tissue, adiponectin, unlike leptin, is decreased with increased visceral obesity (21,52). Adiponectin is reported to be associated with improved insulin regulation, blood glucose, and triglyceride levels (28,42). Elevated leptin and insulin associated with obesity are correlated with lower adiponectin receptor expression, particularly in skeletal muscle and adipose tissue (14,52).…”
mentioning
confidence: 99%